Hydrophilic pore-blocked metal–organic frameworks: a simple route to a highly selective CH4/N2 separation. Issue 4 (8th December 2014) - Kim, Daeok; Lee, Huen
Abstract : Using the difference in the inclusion of CH4 and N2 gases in the hydrophilic pore-blocked Cu3 BTC2, a highly selective CH4 /N2 separation was achieved. Abstract : The separation of gas mixtures with similar thermodynamic and transport properties is a challenging issue. For that, various types of adsorbents and membranes have been introduced. To date, solving this difficult problem remains an urgent core task in the energy and environment fields. Herein, we introduce a simple method to achieve highly selective separation of CH4 /N2 . To demonstrate our concept, a CH4 /N2 mixture was separated by Cu3 BTC2 filled with water, with the water blocking the hydrophilic pore to reject the inclusion of gas molecules having weak affinity for water, and with the empty hydrophobic pores acting as gas storage sites. This led to high equilibrium selectivity of the CH4 /N2 mixture, at 24.7, which is 6 times higher than the untreated Cu3 BTC2 itself. Moreover, the formation of methane hydrate in the mesopore of MOF was observed.